Implementasi Continuity Of Care dalam Pelayanan Kebidanan - Andri Nur Sholihah; Widiastuti Widiastuti; Suparmi Suparmi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Continuity of Care (COC) is a service that is achieved when there is a continuous relationship between a woman and a midwife. Based on PWS-KIA data, the incidence or cases of pathological obstetrics in pregnancy were 12%, cases of childbirth were 13%, cases during the postpartum period were 7.4%, and cases in newborns were 3.7%. However, the implementation of Continuity of Care (COC) at the Health Center itself has never been evaluated. This study is to analyze the implementation of continuity of care in pathological pregnancy services at Primary Health Center. This study was a qualitative descriptive study with 5 midwives and 2 pregnant women as the samples. The data were gathered through a Focus Group Discussion. The results of the analysis were in the form of a narrative. The service mechanism for pregnant women with their own pathological problems is carried out according to the SOP in the Puskesmas. Meanwhile, for pathological cases of pregnancy, a referral will be conducted to a general practitioner and will also be referred to a nutritionist if the pregnant woman has malnutrition problems such as anemia. The study reveals that midwives' knowledge of COC ranged from first heard (surface introduction) of COC to COC as continuous care. The support system in the implementation of continuity of care is cadres. The inhibiting factor in the implementation of continuity of care is that the limited number of midwives at Primary Health Center.